2022
DOI: 10.3390/met12020246
|View full text |Cite
|
Sign up to set email alerts
|

Machinable Leaded and Eco-Friendly Brass Alloys for High Performance Manufacturing Processes: A Critical Review

Abstract: The recent environmental/health and safety regulations placed restrictions of use of hazardous substances on critical manufacturing sectors and consumers’ products. Brass alloys specifically face a challenging issue concerning the elimination of lead (Pb) which has been a critical element affecting both the machinability and overall quality and efficiency of their manufacturing process. The adaptation of novel materials and processing routes in the green economy constitutes a crucial decision for competitive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…Rivets are manufactured with a brass alloy composed primarily of copper and zinc. Although this material is widely used for industrial applications, its use involves high environmental impact, which can be attributed to properties such as corrosion resistance, absence of magnetism, and machinability . Previous studies have reported that brass directly affects marine organisms, which is evidenced by the high levels of impact categories such as freshwater ecotoxicity (FE), freshwater eutrophication (FEut), and marine ecotoxicity (ME) …”
Section: Resultsmentioning
confidence: 99%
“…Rivets are manufactured with a brass alloy composed primarily of copper and zinc. Although this material is widely used for industrial applications, its use involves high environmental impact, which can be attributed to properties such as corrosion resistance, absence of magnetism, and machinability . Previous studies have reported that brass directly affects marine organisms, which is evidenced by the high levels of impact categories such as freshwater ecotoxicity (FE), freshwater eutrophication (FEut), and marine ecotoxicity (ME) …”
Section: Resultsmentioning
confidence: 99%
“…The fluctuation in flank wear breadth increasing metal cutting distances in the turning process of SUS 304 stainless steel utilising MWF coolant with MXene-NFC is shown in Table 6 and 7 [36]. According to the findings, flank wear rises as the length of the incision grows.…”
Section: Analysis Of Tool Wear On Turning Performance Using Mwf and M...mentioning
confidence: 93%
“…The longevity of the cutting tool experiences an upturn as cutting speed, feed rate, and axial depth of cut witness a reduction, as demonstrated by Equations 6 and 7 [36]. Among these factors, feed rate emerges as the most crucial determinant of tool life, closely followed by depth of cut and cutting speed.…”
Section: Development Of Linear Tool Life Model With Mwf and Mxene-nfcmentioning
confidence: 99%
“…The form of chips is perhaps the most crucial factor to consider when evaluating machinability. Discontinuous chip formation favors the efficient disposal of machined material [3,5], contributes to an enhanced surface finish, minimizes tool wear and allows for higher cutting speeds [6]. In brasses, the most widespread practice for the optimization of machinability has been the incorporation of lead (Pb), which promotes fine and discontinuous chip formation during machining.…”
Section: Introductionmentioning
confidence: 99%
“…These act as stress concentration points during the machining process, promoting free-flowing chips and providing lubrication to the cutting tool as Pb is a soft, low-melting-point element, without affecting the mechanical properties of the brass [3,7]. Nevertheless, the negative effects of Pb on human health and the environment have led to changes in legislation regarding the permissible Pb levels in various applications where brass alloys are required [3,4,6,8,9]. Therefore, there is an imperative need to design alternative Cu-based alloys without the addition of harmful elements like Pb without compromising their properties.…”
Section: Introductionmentioning
confidence: 99%